50 years of high performance liquid chromatography: The contribution of the Department of Analytical Chemistry in Pardubice - Jandera, Pavel (University of Pardubice, 2020)
This article surveys the research activities and contributions of the Department of Analytical Chemistry (first at the Institute of Chemical Technology, later at the Faculty of Chemical Technology of the University of Pardubice), to the field of High Performance Liquid Chromatography in the half a century period between 1969 and 2018. The research topics investigated include various theoretical and practical analytical or preparative techniques, in agreement with the general development trends in the field. The attention is focused on the mechanism and predictive modelling of the retention and separation selectivity in the reversed-phase, organic and aqueous normal phase, ion-pairing, salting-out, micellar and mixed-mode liquid chromatography modes. The effects of the stationary phase, of the mobile phases, and of the sample structure on the retention were investigated in detail. The principal point of the research was the development and verification of the new theory of gradient elution. An important part of the recent research activities has been oriented on the theory and practical applications of the new two-dimensional liquid chromatography technique. During the past half a century, new applications of liquid chromatography were developed in the environmental analysis, in the analysis of drugs and their metabolite products, industrial dyes, intermediates, surfactants, of the phenolic antioxidants and plant oils in food and beverages; some attention being also paid to the separation of chiral compounds.
Keywords: phase systems; gradient elution; two-dimensional chromatography